Quantificational measurement and statistic analysis of eggshell color in duck - ZHANG Bao-le; REN Jin-dong; LI Guo-qin; SHI Fang-xiong; LU Li-zhi (浙江大学学报. 农业与生命科学版)
ECR reflectometer was used for quantitative determination of four colors in Jinyun duck-eggshells. Fifty eggs with three points were measured for every color. Results showed that there existed extremely significant differences (P<0.01) in the average values of the reflection coefficient among four group eggshells, and the quantized interval of color reflectance was 80.64-84.42, 77.74-80.64, 74.85- 77.74 and 64.69-74.95 in white, light blue, blue and deep blue eggshells, respectively. Statistic analysis indicated that the middle of the eggshell was the best measurement point of eggshell color, which accuracy reached 0.8394. The regression analysis showed that there was no significant differences (P>0.05) between the reflection coefficient of the eggshells and different measurement time.